The Implementation of the Student Teams Achievement Division (STAD) Model in Islamic Education (PAI) Learning at SMP Ma'arif Bandung - Muchtarom, Muchtarom (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This study aims to describe the implementation of the cooperative learning model STAD (Student Teams Achievement Division) in Islamic Education (PAI) learning at SMP Ma'arif Bandung. The research uses a qualitative method that describes the phenomena observed in the field. Data collection was conducted through direct observation, in-depth interviews with respondents, and documentation studies of relevant materials. The findings indicate that effective lesson planning is crucial for teachers to achieve the learning objectives. This planning includes various activities involving both teachers and students, such as selecting appropriate methods, media, and learning resources to support the learning process. In the implementation phase, the lesson begins with greetings and prayers, followed by checking student attendance and asking about their well-being. The teacher then motivates students to stay engaged in the learning process. The evaluation of the STAD model's application at SMP Ma'arif Bandung is conducted by assessing student participation in discussions, task completion, and presentation performance.